Application of "Hidden Curriculum" through Utilization of the School Environment on the Concept of Environmental Pollution to Improve Student Learning Outcomes - Iin Inayah; Anda Juanda; Yunita Yunita (International Journal of Education and Humanities, 2021)
The curriculum is a complex process consisting of various activities that can access a need and identify a learning outcome. Hidden curriculum has not received more attention, both from the principal, teachers and students. This without us knowing the hidden curriculum has an influence on the process to improve student learning outcomes. The purpose of this study 1) Describe the application of 'hidden curriculum' in the concept of environmental pollution in class X of SMAN 1 Ciwaringin. 2) Describe the differences in the improvement of student learning outcomes implemented by the hidden curriculum through the use of the school environment with those not implemented through the use of the school environment on the concept of environmental pollution in class X 3. school on the concept of environmental pollution in class X. The method used is quantitative methods, from observation, tests and questionnaires. The population of the study was all students from class X. Sampling using simple random sampling, namely X MIPA 2 experimental class amounted to 30 students and X MIPA 3 control classes amounted to 30 students. Recapitulation of the percentage of observation of student activities on average by 84% in the category of "Very High", the application of the "hidden curriculum" very well. The results of the N-Gain N-Gain significance value of 0,000 means that Ho is rejected and Ha is accepted. Based on the data it can be concluded that there are differences in the increase in significant student learning outcomes between the experimental and control classes. Students give a positive response an average value of 82.5% with the criteria "very strong". It is concluded that there is influence on the application of the "hidden curriculum" on the concept of environmental pollution